Dolutegravir pharmacokinetics in pregnant and postpartum women living with HIV - Mulligan, Nikki; Best, Brookie M; Wang, Jiajia; Capparelli, Edmund V; Stek, Alice; Barr, Emily; Buschur, Shelley L; Acosta, Edward P; Smith, Elizabeth; Chakhtoura, Nahida; Burchett, Sandra; Mirochnick, Mark (AIDS (London), 2018)
To evaluate dolutegravir pharmacokinetics during pregnancy compared with postpartum and in infant washout samples after delivery. Ongoing, nonrandomized, open-label, parallel-group, multicenter phase-IV prospective study of antiretroviral pharmacokinetics in HIV-infected pregnant women and infants. Intensive steady-state 24 h pharmacokinetic profiles after dolutegravir 50 mg once-daily were performed during the second trimester (2T), third trimester (3T) and postpartum. Maternal delivery and postnatal infant samples were collected after birth. Dolutegravir was measured by validated LC-MS/MS; quantitation limit was 0.005 μg/ml. A two-tailed Wilcoxon signed-rank test (α = 0.10) was employed for paired within-subject comparisons. Twenty-nine enrolled participants had a median age of 32 years (range 21-42). Pharmacokinetic data were available for 15 (2T), 28 (3T) and 23 (postpartum) women. Median dolutegravir AUC0-24,Cmax and C24 were 25-51% lower in the 2T and 3T compared with postpartum. The median cord blood/maternal plasma concentration ratio was 1.25 (n = 18). In 21 infants, median elimination half-life was 32.8 h after in utero exposure. Viral load at delivery was less than 50 copies/ml for 27/29 women (93%). Twenty-nine infants were HIV-negative. Renal abnormalities noted on ultrasound in two infants were deemed possibly related to dolutegravir. Dolutegravir exposure is lower in pregnancy compared with postpartum in the same women on once-daily dosing. Median AUC0-24 during pregnancy was similar to, whereas trough concentrations were lower than, those seen in nonpregnant adults. Trough concentrations in pregnancy were well above dolutegravir EC90 (0.064 μg/ml). Dolutegravir readily crosses the placenta. Infant elimination is prolonged, with half-life over twice that of historical adult controls.